'There is no Zyzz': the subcultural celebrity and bodywork project of Aziz Shavershian. Issue 1 (2nd January 2017) - Fuller, Glen; Page Jeffery, Catherine
ABSTRACT: Aziz 'Zyzz' Shavershian was an Australian bodybuilder and internet micro-celebrity who died tragically at the age of 22. Shavershian was famous for his body and his internet-based practices of self-representation. This article will examine Shavershian's practices of representation in terms of his online persona, 'Zyzz', as a celebrity bodywork project. We argue that 'Zyzz' is the aspirational 'image' that Shavershian himself embodied and expressed. Followers and fans of 'Zyzz' do not simply want his 'body', they want to live his aspirational bodywork project. We engage with and critically analyse the bodywork project as a unique discursive object characterised by the circulation of affect and enacted through embodied activity. Of interest to us is thinking beyond the individual Aziz Shavershian to appreciating 'Zyzz' as a shared homosocial project that we map in terms of an 'aspirational' trajectory out of the conditions of 'protest masculinity'. The resonant singularities of the 'Zyzz' project circulate in this homosocial cultural context as thresholds of qualitative transformation: there is a transformation of the 'worked' body, a mobilisation of the 'enthusiastic' body, and a valorisation of the 'respected' body.